Editorial - Pacheco, José (2014)
Ready to transmit this Editorial for diagramming, we received an email that tells us the death of Peruvian hematologist Dr. Bertha A. Bouroncle Pereny in Columbus, Ohio, at age 93. The Bouroncle Dr., Graduate School of Medicine, San Fernando, around 1950, had a successful career in science, among others, have identified the cancer called hairy cell leukemia and participate in other discoveries of childhood leukemia.